Monogenic forms of systemic lupus erythematosus: new insights into SLE pathogenesis - Belot Alexandre; Cimaz Rolando (BMC, 2012)
Abstract The pathogenesis of Systemic Lupus Erythematosus (SLE) is complex and remains poorly understood. Infectious triggers, genetic background, immunological abnormalities and environmental factors are all supposed to interact for the disease development. Familial SLE as well as early-onset juvenile SLE studies make it possible to identify monogenic causes of SLE. Identification of these rare inherited conditions is of great interest to understand both SLE pathogenesis and molecular human tolerance mechanisms. Complement deficiencies, genetic overproduction of interferon-α and apoptosis defects are the main situations that can lead to monogenic SLE. Here, we review the different genes involved in monogenic SLE and highlight their importance in SLE pathogenesis.